Effect of a cheese rich in angiotensin-converting enzyme-inhibiting peptides (Gamalost®) and a Gouda-type cheese on blood pressure: results of a randomised trial - Rita Nilsen (Food & Nutrition Research, 2016)
Background: High blood pressure (BP) is the leading risk factor for global disease burden, contributing to 7% of global disability adjusted life years. Angiotensin converting enzyme (ACE)-inhibiting bioactive peptides have the potential to reduce BP in humans. These peptides have been identified in many dairy products and have been associated with significant reductions in BP. Objective: The objective of this trial was to examine whether a cheese rich in ACE-inhibiting peptides (Gamalost®), or a standard Gouda-type cheese could lower BP. Design: A total of 153 healthy participants were randomised to one of three parallel arms: Gamalost® (n=53, 50 g/day for 8 weeks), Gouda-type cheese (n=50, 80 g/day for 8 weeks), and control (n=50). BP and anthropometric measurements were taken at the baseline and at the end, with an additional BP measurement midway. Based on BP at baseline, participants were categorised as having optimal BP (<120/<80 mmHg), normal-high BP (120–139/80–89 mmHg), or being hypertensive (>140/>90 mmHg). Questionnaires about lifestyle, health, and dietary habits were completed at baseline, midway and end. Results: In total, 148 participants (mean age 43, 52% female) completed the intervention. There were no differences among the three groups in relevant baseline characteristics. BP was reduced in the entire study population, but the cheese groups did not differ from control. However, in a subgroup of participants with slightly elevated BP, BP at 4 weeks of intervention seemed to be borderline significantly more reduced in the Gamalost® group compared with the control group (Dunnett test: diastolic BP −3.5 mmHg, 95% confidence interval (CI) −7.3, 0.4, systolic BP: −4.3 mmHg, 95% CI −9.8, 1.1). Conclusion: An intention-to-treat analysis of the data showed no cheese effect upon BP compared to control, but Gamalost® seemed to have a small, non-significant lowering effect on diastolic BP after 4 weeks in people with a normal-high BP.